2020
DOI: 10.1097/jcma.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

CircularRNA as novel biomarkers in liver diseases

Abstract: The liver is an essential organ that is primarily responsible for digestion and eliminating toxic substances from the body. After the industrial revolution, Western diet and lifestyle changes have increased the incidence of several liver diseases, including non-alcoholic fatty liver disease (NAFLD), non-alcoholic steatohepatitis (NASH), liver cirrhosis, and hepatocellular carcinoma (HCC). NAFLD and NASH are mostly asymptomatic at early stages, and the disease progression from NAFLD to life-threatening HCC rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…29 CircRNAs are implicated in the progression of liver diseases including HCC via regulating various cell events. 30 A previous study suggested that circ_0006916 played an important role in HCC development. 15 In this study, we found that circ_0006916 could repress HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…29 CircRNAs are implicated in the progression of liver diseases including HCC via regulating various cell events. 30 A previous study suggested that circ_0006916 played an important role in HCC development. 15 In this study, we found that circ_0006916 could repress HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…It is a unique type of single-stranded lncRNA arranged in a closed loop structure, which is highly stable and resistant from RNA degrading enzymes [80,81]. In recent years, increased research has focused on the role of circRNAs as ceRNA or miRNA sponges, revealing their strong association with the development of various diseases and their possible use as diagnostic biomarkers [82][83][84]. The first report indicating an involvement of circRNAs in liver fibrosis comes from Chen and colleagues [85], who indentified differentially expressed circRNAs associated with HSC activation.…”
Section: Circular Rnas (Circrnas)mentioning
confidence: 99%
“…A certain number of circRNAs have been discovered as potential biomarkers or therapeutic targets for HCC [36][37][38][39][40][41][42][43]. As well as for HCC, circRNAs play an important role in non-neoplastic chronic liver diseases, such as ALD, MAFLD, liver fibrosis, and autoimmune diseases through epigenetic mechanisms [11,12,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%